(untitled) (Archive of Conferences, 2021)
The article scientifically analyzes the main problems and new approaches to increasing the creative activity of young people. The criteria for creativity are: fluency, characterized by the amount of ideas generated per unit of time; originality - the ability to generate “unique” ideas; susceptibility - sensitivity to unusual details and contradictions; metaphorism - the willingness to work in a fantastic, «impossible» context, the tendency to use symbolic, associative means to express thoughts. Creative management decisions are management decisions, a development process that is creative, and results imply positive outcomes for results.